O procedimento jurisdição voluntária para homologação judicial de acordo extrajudicial na Justiça do Trabalho - Morais, Rafaela Rodrigues de (2020)
The purpose of this work is to study one of the innovations brought by Law 13.467/2017: the voluntary jurisdiction procedure for judicial ratification of an extrajudicial agreement. To do this, we will initially go through relevant issues that gravitate towards the topic, which are the methods of conflict resolution, availability of labor rights, waiver and transaction. Soon after, we will make an analysis of articles 855-B to E of the Consolidation of Labor Laws called “Do Processo De Jurisdição Voluntária Para Homologação De Acordo Extrajudicial”. At the end, the main current debates on the topic will be presented, as well as the jurisprudential position of the Superior Labor Court